Penggunaan Game AI (Kahoot) untuk Meningkatkan Literasi Membaca SD Negeri Kalipenten - Fajar Maulana (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2024)
Learning media continues to develop along with the development of the times. Therefore, as teachers and educators, they must be able to adjust and learn related to learning media that continues to develop. The use of learning media with the use of modern technology has various types, one of which is kahoot learning media. This research is focused on how to find out the advantages, disadvantages, and impacts used in kahoot game applications. The method used for this sniffing is a quantitative descriptive method that contains a description of the explanation related to the advantages, disadvantages, and impacts used for the kahoot application. The results of the study found that the game has advantages, namely attractiveness, novelty, and reducing boredom. The disadvantage of kahot games is that they do not explore the area of children's reasoning comprehensively, as opposed to the essential construction. From this study, the conclusion is that this learning media has distinctive advantages and disadvantages, teachers must adjust the use of appropriate learning media and plan so that the impact can be appropriate effectively and efficiently